Efeitos da Dopagem Aliovalente com Ba+2 no sistema Bi5Ti3FeO15: estrutura de defeitos e influência nas propriedades ferroicas - Barbosa, Vitor (Universidade Federal de São Carlos, 2025)
Multiferroic systems have attracted increasing attention because they allow the coexis tence of properties such as ferroelectricity and magnetism in a single material. Among them, Bi5Ti3FeO15 (BFT4), a member of the four-layer Aurivillius family composed of perovskite blocks interspersed with fluorite-like layers, stands out for exhibiting multiferroicity at room temperature. Consequently, the search for structural modification strategies at the atomic level has intensified in recent years, aiming to understand and control the physical behavior of these materials. In this work, we investigate the effects of alliovalent substitution of Bi3+ by Ba2+ in the BFT4 system, focusing on understanding how local distortions and changes in the defect structure influence its electrical and ferroic properties. Samples with different atomic substitution contents (0,0%, 0,6%, 3,0%, and 4,0%) were sintered via solid-state reaction and characterized by X-ray diffraction, dilatometry, impedance spectroscopy, ferroelectric hysteresis measurements, and magnetometry. From a structural point of view, Ba2+ incorporation was shown to be viable up to approximately 4%. Crystallographic refinement revealed a preferential redistribution of barium ions between the fluorite and perovskite layers, with an increasing tendency to occupy the perovskite as the doping level increased. This behavior was associated both with the relief of the internal strain generated by the mismatch between the layers and with an increased concentration of defects in this region. As the barium content increased, a progressive symmetrization of the structure was observed, accompanied by a reduction in spontaneous polarization, partially compensated by cationic disorder, and a gradual decrease in the paraelectric-ferroelectric transition temperature. As predicted by the charge compensation mechanism, impedance spectroscopy measurements indicated a progressive increase in the concentration of oxygen vacancies, reflected in the increased ionic conductivity of the system. These defects showed a strong impact on the ferroelectric behavior, acting as domain pinning centers, as evidenced by the P–E curves and dielectric responses. Finally, the nature of the magnetic interactions, predicted by the antisymmetric exchange interaction, proved sensitive to the structural modifications induced by doping, since symmetrization favored the modulation of the magnetic properties. In summary, the results demonstrate that Ba2+ doping constitutes an effective route for engineering the ferroic properties of BFT4, through both structural distortions and controlled creation of defects, contributing to a more comprehensive understanding of the multiferroicity in this system.
Effects of Ba+2 Alliovalent Doping on the Bi5Ti3FeO15 system: defect structure and influence on ferroic properties
Keywords: Multiferroico; Magnetoelétrico; Dopagem; Aliovalente; Aurivillius; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS DIELETRICOS E PROPRIEDADES DIELETRICAS